2021
DOI: 10.1108/bjm-08-2020-0314
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-spanning search, knowledge integration capability and sustainable competitive advantage

Abstract: PurposeThe purpose of this paper is to investigate how boundary-spanning search affects sustainable competitive advantage under the conditions that competitors also search and to test the moderating role of knowledge integration capability.Design/methodology/approachThis paper classifies boundary-spanning search into proactive search and responsive search by considering competition and develops a theoretical model in which knowledge integration capability moderates the effects of proactive and responsive searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Moreover, the measurement of exploratory learning (EY) and exploitative learning (EE) was prepared and adopted from Atuahene-Gima and Murray (2007) and Chung et al (2015) . Lastly, the measurement of the sustainable competitive advantage (SCA) mainly referred to Yang and Wang (2020) and Yang et al (2021) . This study conducted a tick-the-box survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the measurement of exploratory learning (EY) and exploitative learning (EE) was prepared and adopted from Atuahene-Gima and Murray (2007) and Chung et al (2015) . Lastly, the measurement of the sustainable competitive advantage (SCA) mainly referred to Yang and Wang (2020) and Yang et al (2021) . This study conducted a tick-the-box survey.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, previous studies have suggested that a firm’s ambidextrous learning and the competitive advantage may be influenced by firm age ( age ), firm size ( size ), ownership ( ownership ), and industry characteristics ( Camisón and Villar-López, 2014 ; Ma and Wu, 2020 ; Yang and Wang, 2020 ). For industry characteristics ( industry ), relevant research should compare high-tech and other industries ( Ge et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturers are facing an environment with blurred boundaries and inseparable internal and external resources [50]. For manufacturing enterprises, boundary spanning behavior has become an important way to obtain sustainable competitive advantage in the Internet era [53]. In the Internet era, the change of information acquisition and circulation mode has broken the original market structure.…”
Section: E Mediating Role Of Boundary Spanning Behavior On the Relati...mentioning
confidence: 99%
“…Secondly, knowledge integration is also an effective means to improve the utilization of customer knowledge and avoid R&D risks in the process of customer participation affecting NPD performance. Through the integration of new and old internal and external knowledge, enterprises can increase the possibility of recombination of knowledge elements and form enterprise-specific tacit knowledge, thereby promoting the establishment of sustainable competitive advantages [12]. And the stronger the ability of knowledge integration is, the higher the efficiency of knowledge circulation in an organization will be, which is conducive to the accurate evaluation and utilization of the acquired knowledge by an enterprise, thus effectively reducing the uncertainty in the NPD process and improving the enterprise performance [13].…”
Section: The Mediating Role Of Knowledge Integrationmentioning
confidence: 99%